Kepastian Hukum terhadap Covernote dalam Perjanjian Kredit Perbankan - Nur Syifa Islamiya Effendi; Anang Shophan Tornado (Lembaga Yasin AlSys, 2026)
Although the use of covernotes in bank credit agreements has become an established practice in Indonesia, studies examining their legal status, legal certainty, and regulatory model remain limited. This study aims to analyze the status of covernotes in bank credit agreements and formulate an ideal regulatory model to ensure legal certainty for the parties. The study employed a descriptive-analytical normative legal method using statutory and conceptual approaches. Legal materials were collected through a literature review and analyzed qualitatively using Gustav Radbruch’s and Jan Michiel Otto’s theories of legal certainty and Hans Kelsen’s theory of legal responsibility. The findings indicate that a covernote has the status of an innominate agreement that is accessory to the principal credit agreement and binds the parties pursuant to Article 1338 of the Indonesian Civil Code. However, its legal certainty remains inadequate because no normative provisions explicitly regulate its status, form, time limit, and legal consequences. This uncertainty is reflected in the differing legal considerations between Supreme Court Decision Number 4242 K/Pid.Sus/2023 and Supreme Court Decision Number 1233 K/Pid.Sus/2019. The ideal regulation of covernotes should be based on the principles of legal certainty, justice, accountability, and proportionality through a three-tier regulatory model, namely the revision of the Notary Office Law, the formulation of comprehensive Financial Services Authority regulations, and the establishment of professional standards by the Indonesian Notary Association. These findings contribute to the development of notarial and banking law studies by clarifying the legal vacuum surrounding the use of covernotes. This study affirms that the normative recognition and regulation of covernotes are necessary to provide legal protection for the parties and serve as a basis for policy formulation by legislators, the Financial Services Authority, and notarial professional organizations.